2021
DOI: 10.3390/nu13062013
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Relation between Double Fortification of Wheat Flour with Iron and Folic Acid, and Markers and Prevalence of Anemia in Children

Abstract: Fortification of wheat flour with iron and folic acid became mandatory in Ivory Coast in 2007. The purpose of this study was to determine the time trend relation between mandatory double fortification of wheat flour with iron and folic acid and markers and prevalence of anemia by comparing the data between pre- and post-fortification periods in Ivory Coast children. Data were derived from the pediatric unit of the University Hospital of Treichville, Abidjan, Ivory Coast. Medical records of 467 children from 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Several studies have shown that, especially in low-income countries, iron food fortification, referring to the addition of iron alone or with other micronutrients during food processing, was a safe and cost-effective way of preventing ID despite some technical difficulties related to undesirable changes in the food, such as alterations in appearance and taste [10,82,[141][142][143][144][145][146]. Thus, various commonly consumed foods have been fortified in addition to formula, mainly cereals [10,82,92,93,142,147,148], but also wheat flour [143,145,146,149,150], maize flour [151], rice [143,146,152,153], soy sauce or fish sauce [146,[154][155][156], salt [157,158], and candies [159]. Such strategies may, however, have a limited impact in infants and young toddlers due to their relatively low staple food consumption and even lower seasoning and condiment intake [160].…”
Section: Fortified Foods Addition Of Iron To Staple Foodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that, especially in low-income countries, iron food fortification, referring to the addition of iron alone or with other micronutrients during food processing, was a safe and cost-effective way of preventing ID despite some technical difficulties related to undesirable changes in the food, such as alterations in appearance and taste [10,82,[141][142][143][144][145][146]. Thus, various commonly consumed foods have been fortified in addition to formula, mainly cereals [10,82,92,93,142,147,148], but also wheat flour [143,145,146,149,150], maize flour [151], rice [143,146,152,153], soy sauce or fish sauce [146,[154][155][156], salt [157,158], and candies [159]. Such strategies may, however, have a limited impact in infants and young toddlers due to their relatively low staple food consumption and even lower seasoning and condiment intake [160].…”
Section: Fortified Foods Addition Of Iron To Staple Foodsmentioning
confidence: 99%
“…Several biases were, however, acknowledged by the authors, mainly linked to the fact that most of the studies were performed in malaria-endemic zones and/or in areas with a low prevalence of ID. Results with fortified flour are even more inconsistent [141,145,146,149,150].…”
Section: Fortified Foods Addition Of Iron To Staple Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an observational study that compared the prevalence of anemia in children before and after double fortification of wheat flour with folic acid and iron, no significant difference was found in mean hemoglobin concentrations between pre-fortification and post-fortification. However, MCV concentrations increased significantly in the post-fortification period from the pre-fortification period (from 76.8 fL to 79.1 fL; p = 0.02) [ 30 ]. Another study used NHANES data to evaluate the prevalence of anemia and macrocytosis before and after folic acid fortification (1988–1994 vs. 1999–2004) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Folic acid has been demonstrated to promote the formation of red blood cells and play important roles in protein synthesis, cell division, and growth ( 64 , 65 ). Folic acid deficiency can cause megaloblastic anemia and affect hemoglobin production and cell maturation in red blood cells ( 65 , 66 ). Currently, folic acid is widely used in animal husbandry due to various important physiological functions.…”
Section: Discussionmentioning
confidence: 99%